Superbugs and antibiotics in the newborn - Alessandro Borghesi; Mauro Stronati (Hygeia Press di Corridori Marinella, 2015)
Antibiotic resistance has become an urgent and global issue, with 700,000 deaths attributable to multidrug-resistance occurring each year worldwide. The overuse of antibiotics, both in animal industry and in clinical settings, and the generated selective pressure, are the main factors implicated in the emergence of resistant strains. The Centers for Disease Control and Prevention (CDC) have pointed out that more than half of hospital patients receive an antibiotic during their stay, and nearly a third receive a broad-spectrum antibiotic. In neonatal units, previous antibiotic exposure to third-generation cephalosporin and carbapenem were identified as independent risk factors for infection caused by multi-drug resistant strains. While resistant 'superbugs' emerge, the arsenal to fight these microorganisms is progressively shrinking, as the number of newly discovered antibiotics approved by the Food and Drug administration each year is dropping. In face of global spread of antibiotic resistance and of the limited development of new drugs, policies and rules are under study by agencies (CDC, World Health Organization) and governments, in order to: i) facilitate and foster the discovery of new antibiotic compounds; ii) develop new, alternative therapies able to potentiate or modulate the host immune response or to abrogate the resistance and virulence factors in the microorganisms; and iii) prevent the emergence of resistance through antibiotic stewardship programs, educational programs, and reduction of antibiotic use in livestock; the field of neonatal medicine will need its own, newborn-tailored, antibiotic stewardship programs to be implemented in the NICUs.   Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA)